(untitled) (Vietnam Journal of Community Medicine, 2024)
Background: The increasing prevalence of mental disorders has highlighted the urgent need to enhance the quality of community-based mental health care. Objective: To evaluate the quality of community-based mental health services provided at commune health stations in Ben Tre province. Methods: A cross-sectional study design was employed to collect data from 157 commune health stations. Results: The community-based mental health program at commune health stations in Ben Tre has achieved relatively high outcomes, particularly in terms of treatment efficacy and functional recovery of patients. However, the quality of mental health care services still has limitations, especially in screening, case management, and rehabilitation. Factors influencing the quality of care include the qualifications of healthcare providers, supervision, and resource availability. Conclusion: To improve the quality of mental health care services, there is a need to enhance the capacity of healthcare workers, strengthen supervision, ensure adequate resources, and establish effective inter-sectoral coordination mechanisms.